(untitled) (Ustozlar uchun, 2026)
This article examines the role of extra-linguistic factors in the semantic transformation of idiomatic compounds in English and Uzbek languages. Extra-linguistic factors refer to social, cultural, historical, psychological, and pragmatic influences that exist outside the language system but significantly affect meaning formation and change. Idiomatic compounds, as culturally embedded and figurative expressions, are particularly sensitive to such influences. The study focuses on how social change, historical events, cultural traditions, globalization, media, and bilingual environments contribute to the reinterpretation and semantic shift of idioms in both languages. Using a comparative approach, the article analyzes selected idiomatic expressions to demonstrate how changes in lifestyle, values, and communication practices reshape idiomatic meaning over time. Special attention is paid to the influence of cultural worldview, national mentality, and collective experience reflected in idioms. The research also discusses the impact of translation and intercultural interaction on idiomatic adaptation. The findings suggest that extra-linguistic factors play a decisive role in idiom evolution, often leading to metaphorical recontextualization or pragmatic refunctionalization. This study contributes to contrastive phraseology and offers valuable insights for translators, language teachers, and researchers interested in idiom semantics and cultural linguistics.